Proceedings : Post Pandemic Challenges in Embracing Society 5.0 - Toha, Siti Fauziah (Persatuan Saintis Muslim Malaysia (PERINTIS), 2023)
This year's conference theme, "Post Pandemic Challenges in Embracing Society 5.0," serves as a guiding light for our collective exploration of the diverse factors that contribute to universal well-being. Through insightful presentations, thought-provoking discussions, and collaborative networking, ICUW 2022 aims to foster a deeper understanding of the intricate interplay between physical, mental, emotional, social, and environmental aspects of wellbeing. By bringing together experts from various disciplines, we seek to nurture a rich and interdisciplinary dialogue that can pave the way for groundbreaking advancements in the field.